EFFECTIVENESS OF USING ZOOM IN CREATIVE BROADCAST MANAGEMENT LEARNING AT STIKOM INTERSTUDI - Maulana, Akhdan Hadi; Surasmi, Rahayu (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
Communication and information have developed to date, starting from the agricultural technology era, the industrial era and the digitalization era. The aim of this research is to determine the effectiveness of using Zoom Meetings as a media platform in learning creative broadcast management courses for STIKOM Interstudi students majoring in broadcast class 2020. This research uses a qualitative descriptive approach and collects data through in-depth interviews. The concept used is adopted from Djamarah in Syatra (2013) to measure effectiveness in online learning with the indicators; a) the existence of clear learning objectives, b) lecturer's ability to manage the learning process, c) student involvement during the learning process, and d) student responses or responses. The results of this research explain that the use of the Zoom Meeting platform in learning Creative Broadcast Management is quite effective. Judging from the fact that the learning objectives are clear enough to be effective, the lecturer's ability to manage learning is also quite good, where the lecturer can master the learning material, students are also actively involved in the teaching and learning process so that there is feedback or response between the lecturer and students.